The growing threat of multidrug-resistant coagulase-negative Staphylococcus spp. on hospital lift buttons in Malaysia - Muhammad, Izzati; Samsuddin, Niza; Raja Abdul Rahman, Raja Noor Zaliha; Kamarudin, Norhidayah; Alias, Norsyuhada (Malaysian Society for Microbiology, 2025)
Aims: This study investigated the presence of coagulase-negative Staphylococcus spp. (CoNS) and its antimicrobial resistance properties, isolated from lift buttons in public and teaching hospitals in Pahang, Malaysia. Methodology and results: Purposive swab sampling was conducted thrice at two-week intervals. The samples were processed using standard microbiological methods to identify the species. Antimicrobial susceptibility testing was performed using the Kirby-Bauer disc diffusion method. CoNS resistant to cefoxitin (4/16) were further analyzed for the presence of the methicillin-resistance gene (mecA) through polymerase chain reaction (PCR). Seven Staphylococcus species were identified from 16 isolates and classified as CoNS, which are commonly found as part of the human skin microbiome. Approximately 82% (13/16) of the CoNS exhibited antibiotic resistance, including resistance to penicillin, fusidic acid, and erythromycin. Staphylococcus haemolyticus had a higher multiple antibiotic resistance (MAR) index than the others, suggesting it originated from a high-risk contamination source, likely associated with heavy antibiotic usage. Among the four cefoxitin-resistant CoNS, S. haemolyticus was resistant to nine antibiotic classes and carried the mecA gene. The other three CoNS were resistant to four antibiotic classes. Conclusion, significance and impact of study: This study highlights the presence of multidrug-resistant (MDR) CoNS on hospital lift buttons, posing an increased risk of severe infection for immunocompromised patients. Future research should focus on elucidating the mechanisms of antibiotic resistance in MDR CoNS, assessing the efficacy of current antimicrobial treatments, and implementing continuous surveillance to monitor the spread of resistance.